Effect of different chemical treatments on nutritional and antinutritional properties of coffee pulp - Ulloa Rojas, J.B. (2002)
Different chemical treatments were tested to improve the nutritional value of coffee pulp (CoP): (1) alkali, NaOH solutions of 5 and 10% for 24 and 48 h; (2) a combination of acid and alkali, with first a treatment with HCl (1.5 and 3 M for 24 and 48 h), followed by a NaOH solution of 5% for 48 h; (3) A combination of alkali and ensilage, with first a treatment with a NaOH solution of 5% for 48 h, followed by ensilage with molasses (50 and 100 g molasses/kg of CoP) for 2 and 3 months. The CoP treated with NaOH alone or with the combination HCl–NaOH showed higher contents of ash, fat and cellulose but lower contents of antinutritional factors (ANFs) (polyphenols, tannins and caffeine) than oven-dried-CoP (OD-CoP) (P < 0.05). The true protein content in the CoP was not affected by the alkali treatment but was reduced in the acid–alkali treated CoP compared to OD-CoP. A combined treatment with alkali-ensilage resulted in higher true protein, fat and ash contents (P < 0.05) and in similar contents of cellulose than in OD-CoP. Polyphenols, tannins and caffeine contents were lower in treated CoP than in OD-CoP, but there was no difference in the size of the effect for caffeine between one treatment to the other. The higher ash content found in alkali-ensiled CoP could result from the addition of the alkali. The reduction of ANFs was much higher in the chemical treated CoP than in the alkali-ensiled CoP. The alkali treatment yielded the best overall results in upgrading the nutritive value of CoP. © 2002 Elsevier Science B.V. All rights reserved.